Associations between MRI-defined synovitis, bone marrow lesions and structural features and measures of pain and physical function in hand osteoarthritis. Issue 6 (25th November 2011) - Haugen, Ida Kristin; Bøyesen, Pernille; Slatkowsky-Christensen, Barbara; Sesseng, Sølve; van der Heijde, Désirée; Kvien, Tore K
Abstract : Objectives: To explore associations between MRI features and measures of pain and physical function in hand osteoarthritis (OA). Methods: Eighty-five patients (77 women) with mean (SD) age of 68.8 (5.6) years underwent contrast-enhanced MRI of the interphalangeal joints (dominant hand) and clinical joint assessment. One investigator read the MRIs for presence/severity of osteophytes, joint space narrowing, erosions, bone attrition, cysts, malalignment, synovitis, flexor tenosynovitis, bone marrow lesions (BMLs) and ligament discontinuity according to the proposed Oslo hand OA MRI score. Pain and physical function were assessed by joint palpation (tenderness yes/no), self-reported questionnaires (Australian/Canadian (AUSCAN) hand index, Functional Index of hand osteoarthritis (FIHOA), Arthritis Impact Measurement Scale-2 (AIMS-2) hand/finger) and grip strength. Logistic regression with generalised estimating equations was used to explore associations between the presence of MRI features and joint tenderness, and linear regression for associations between the burden of MRI abnormalities and patient-reported outcomes and grip strength (adjusted for age and sex). MRI features with p<0.25 were introduced into a multivariate model. The final model included features with p≤0.10 (backward selection). Results: MRI-defined moderate/severe synovitis (OR=2.4; p<0.001), BMLs (OR=1.5; p=0.06), erosions (OR=1.4; p=0.05), attrition (OR=2.5; p<0.001) and osteophytes (OR=1.4; p=0.10) were associated with joint tenderness independently of each other (final model adjusted for age and sex). The sum score of MRI-defined attrition was associated with FIHOA (B=0.58; p=0.005), while the sum score of osteophytes was associated with grip strength (B=−0.39; p<0.001). No significant associations were found with AUSCAN pain/physical function or AIMS-2 hand/finger subscales. Conclusion: MRI-defined synovitis, BMLs, erosions and attrition were associated with joint tenderness. Synovitis and BMLs may be targets for therapeutic interventions in hand OA.